Crystal structure of catena-poly[[[diaquacobalt(II)]-bis(μ-hex-3-enedinitrile-κ2N:N′)] bis(tetrafluoridoborate)] - Jung-Su Son; Sung-Chul Lim; Hochun Lee; Seung-Tae Hong (Acta Crystallographica Section E: Crystallographic Communications, 2015)
In the structure of the title salt, [Co(C6H6N2)2(H2O)2](BF4)2, the CoII atom is located on an inversion centre. The transition metal is in a slightly distorted octahedral coordination environment, defined by the cyano N atoms of four hex-3-enedinitrile ligands in equatorial positions and the O atoms of two water molecules in axial positions. The bridging mode of the hex-3-enedinitrile ligands leads to the formation of cationic chains extending parallel to [1-10]. The BF4− counter-anion is disordered over two sets of sites [occupancy ratio = 0.512 (19):0.489 (19)]. It is located in the voids between the cationic chains and is connected to the aqua ligands of the latter through O—H...F hydrogen bonds. One methylene H atom of the hex-3-enedinitrile ligand forms another and weak C—H...O hydrogen bond with a water O atom of a neighbouring chain, thus consolidating the three-dimensional network structure.